A&T Gujarat Implementation Research Baseline Survey 2022: Supervisory Cadre - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
This dataset originates from the Supervisory Cadre Survey, conducted as part of the baseline for the Alive & Thrive (A&T) impact evaluation study in Gujarat, India. The survey collected data from various supervisory roles, including Mukhya Sevika (MS), ASHA Facilitators (ASHA-F), Auxiliary Nurse Midwives (ANMs), Female Health Supervisors (FHS), Taluka Health Visitors (THVs), Child Development Project Officers (CDPOs), District Program Officers (DPOs), Taluka Health Officers (THOs), and Chief District Health Officers (CDHOs).